Canopy architecture and water productivity in sorghum - Narayanan, Sruthi (Kansas State University, 2011)
Increasing crop water use efficiency (WUE), the amount of biomass produced per unit water consumed, can enhance crop productivity and yield potential. The objective of the first study was to evaluate the factors affecting water productivity among eight sorghum (Sorghum bicolor (L.) Moench) genotypes, which differ in canopy architecture. Sorghum genotypes, grown under field conditions, showed significant differences in (a) biomass production, (b) water use, (c) intercepted radiation, (d) water productivity and (e) radiation use efficiency (RUE; the amount of biomass produced per unit of intercepted radiation which is suitable for photosynthesis). WUE and RUE were more strongly correlated to biomass production than to water use or intercepted radiation, respectively. RUE was positively correlated to WUE and tended to increase with internode length, the parameter used to characterize canopy architecture. These results demonstrate that increased utilization of radiation can increase water productivity in plants. Sorghum canopies that increase light transmission to mid−canopy leaves can increase RUE and also have the potential to increase crop productivity and WUE. The objective of the second study was to develop a quantitative model to predict leaf area index (LAI), a common quantification of canopy architecture, for sorghum from emergence to flag leaf stage. LAI was calculated from an algorithm developed to consider area of mature leaves (leaves with a ligule/collar), area of expanding leaves (leaves without a ligule/collar), total leaf area per plant and plant population. Slope of regression of modeled LAI on observed LAI varied for photoperiod sensitive (PPS) and insensitive (non−PPS) genotypes in 2010. A good correlation was found between the modeled and observed LAI with coefficient of determination (R[superscript]2) 0.96 in 2009 and 0.94 (non−PPS) and 0.88 (PPS) in 2010. These studies suggest that canopy architecture has prominent influence on water productivity of crops and quantification of canopy architecture through an LAI simulation model has potential in understanding RUE, WUE and crop productivity.
Keywords: Sorghum; water use efficiency; radiation use efficiency; productivity; internode length; Leaf area; Agriculture, General (0473); Agronomy (0285)